10.36873/jht.v15i2.2159 Yunik Istikorini, Arum Sekar Wulandari, Wahyu Krisna: UJI KESEHATAN BENIH KENANGA YLANG-YLANG (Cananga odorata Lam. Hook.f. & Thomson) forma genuina (Health test of Kenaga Ylang-Ylang Seed (Cananga odorata Lam. Hook.f. & Thomson) forma genuina) - JHT, Admin (Jurnal Hutan Tropika, 2020)
Ylang-ylang (Cananga odorata Hook.F.& Thomson) is one of the defense plants with various benefits and advantages. One of the hallenges in ylang-ylang Cananga cultivation is the contribution of high-quality seed. The study aimed to determine the health of seeds and identify fungi carried by ylang-ylang seeds. The seed health test used an incubation method on potato dextrose agar (PDA) media. Results showed that ylangylang seeds associated with five fungal for 11 months of age and newly harvested seedswere the same fungal. Those isolated fungal were Aspergillus niger, A. flavus, Penicillium sp., Botryodiplodia sp. and Paecilomyces sp. The fungus A. niger is the dominant fungus. Fungi Paecilomyces sp. and Botryodiplodia sp. The fungus A. niger identified most frequently. Fungi Paecilomyces sp. and Botryodiplodia sp. had a fast growth rate, whereas Penicillium sp. had slower growth compared with other isolates. Keywords: Fungus, seed health, ylang-ylang seeds